Modulation of Wnt/β-catenin signaling and proliferation by a ferrous iron chelator with therapeutic efficacy in genetically engineered mouse models of cancer - Coombs, G.; Schmitt, A.; Canning, C.; Alok, A.; Low, I.; Banerjee, N.; Kaur, S.; Utomo, V.; Jones, C.; Pervaiz, Shazib; Toone, E.; Virshup, D. (Nature Publishing Group, 2012)
Using a screen for Wnt/β-catenin inhibitors, a family of 8-hydroxyquinolone derivatives with in vivo anti-cancer properties was identified. Analysis of microarray data for the lead compound N-((8-hydroxy-7-quinolinyl) (4-methylphenyl)methyl)benzamide (HQBA) using the Connectivity Map database suggested that it is an iron chelator that mimics the hypoxic response. HQBA chelates Fe2+ with a dissociation constant of ~10-19 M, with much weaker binding to Fe3+ and other transition metals. HQBA inhibited proliferation of multiple cell lines in culture, and blocked the progression of established spontaneous cancers in two distinct genetically engineered mouse models of mammary cancer, MMTV-Wnt1 and MMTV-PyMT mice, without overt toxicity. HQBA may inhibit an iron-dependent factor that regulates cell-type-specific β-catenin-driven transcription. It inhibits cancer cell proliferation independently of its effect on β-catenin signaling, as it works equally well in MMTV-PyMT tumors and diverse β-catenin-independent cell lines. HQBA is a promising specific intracellular Fe2+ chelator with activity against spontaneous mouse mammary cancers.